The Authority of Al-Sima' in Ushul An-Nahwi: An Analysis of Al-Suyuthi's Thought in the Book Al-Iqtirah: Otoritas Al-Sima' dalam Ushul An-Nahwi: Analisis Pemikiran Al-Suyuthi dalam Kitab Al-Iqtirah - Ashar, Andi Muhammad; Hamzah, Andi Abdul (Al-Wasil, 2025)
Nahwu (Arabic grammar) is a fundamental discipline in Islamic studies, particularly for understanding the Qur'an and Hadith. Debates regarding authoritative sources for establishing grammatical rules have long existed, with the concept of al-sima' (direct reception from eloquent native Arab speakers) being a primary foundation. This research aims to analyze the concept of al-sima' according to Imam Jalaluddin al-Suyuthi (d. 911 H/1505 M) in his work "Al-Iqtirah fi Ushul al-Nahwu". The method employed is a textual analysis of Al-Iqtirah and related literature. The findings indicate that Al-Suyuthi defines al-sima' as any speech trusted for its eloquence (fasahah), encompassing the Qur'an, Prophetic Hadith, and the speech of Arabs up to a certain period before linguistic corruption. The criteria for valid al-sima' include eloquence and source authenticity. Al-sima' has a close relationship with other nahwu sources such as qiyas (analogy), ijma' (consensus), and istishhab (presumption of continuity), with the Qur'an taking precedence in cases of conflict. Al-Suyuthi also applied al-sima' in linguistic analysis, including the acceptance of qira'at syadz (irregular Qur'anic readings) as proof (hujjah) as long as they do not contradict qiyas. In conclusion, al-sima' constitutes a primary authoritative source in Ushul An-Nahwi according to Al-Suyuthi, with clear criteria and applications in the formation of Arabic grammatical rules.